Hubungan Pemenuhan Kebutuhan Nutrisi terhadap Gejala Konstipasi pada Anak dengan Suspect Hirschsprung - Heri Bahtiar; Winda Nurmayani; Maelina Ariyanti; Monalyssa Monalyssa (Institut Kesehatan YARSI Mataram, 2024)
Hirschsprung disease is a disorder of the nervous system in the lower colon, which starts from the anus to the upper intestine and is congenital. Hirschsprung's disease is a rare condition that causes feces to become trapped in the large intestine. The incidence of Hirschsprung occurs between 1 per 2,000 to 1 per 12,000 live births. The most common symptoms of Hirschsprung disease include constipation. Common causes of constipation are failure to respond to the urge to defecate and lack of fiber and fluid intake. The Purpose of this research is to determine the relationship between meeting nutritional needs and symptoms of constipation in children with Suspect Hirschsprung. This research is a descriptive quantitative research with a retrospective research model with a total of 60 respondents and took place at the Children's Surgery Polytechnic, Provincial Hospital. NTB. The results of this study found that children with Good Nutritional Needs Meeting more than Children with Less Nutritional Needs Meeting which is as much as 55%, while children who experience Constipation Symptoms more than children who do not experience constipation symptoms which is as much as 58.3% and the results of the Chi Square correlation test obtained p-value results of 0.025 less than 0.05 significance values which means that both variables are significantly correlated. There are suggestions for the public to pay more attention to the symptoms of disorders that occur in children, such as symptoms of constipation in children, hard stools and immediately take the child to the hospital if there are serious complaints so that they can be treated immediately. ABSTRAK Penyakit Hirschsprung merupakan kelainan sistem saraf pada usus besar bagian bawah, dimulai dari anus hingga usus bagian atas dan bersifat bawaan. Penyakit Hirschsprung adalah suatu kondisi langka yang menyebabkan tinja terperangkap di usus besar. Insiden Hirschsprung terjadi antara 1 per 2.000 hingga 1 per 12.000 kelahiran hidup. Gejala penyakit Hirschsprung yang paling umum adalah sembelit. Penyebab umum sembelit adalah kegagalan respon terhadap keinginan buang air besar dan kurangnya asupan serat dan cairan. Tujuan penelitian ini adalah untuk mengetahui hubungan pemenuhan kebutuhan gizi dengan gejala konstipasi pada anak Suspect Hirschsprung. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan model penelitian retrospektif dengan jumlah responden 60 orang dan bertempat di Politeknik Bedah Anak RSUD Provinsi. NTB. Hasil penelitian ini didapatkan bahwa anak dengan Pemenuhan Kebutuhan Gizi Baik lebih banyak dibandingkan Anak dengan Pemenuhan Kebutuhan Gizi Kurang yaitu sebanyak 55%, sedangkan anak yang mengalami Gejala Sembelit lebih banyak dibandingkan anak yang tidak mengalami gejala konstipasi yaitu sebanyak 58,3 % dan hasil uji korelasi Chi Square diperoleh hasil p-value sebesar 0,025 lebih kecil dari nilai signifikansi 0,05 yang berarti kedua variabel berkorelasi signifikan. Saran bagi masyarakat untuk lebih mewaspadai gejala gangguan yang terjadi pada anak seperti gejala sembelit pada anak, feses keras dan segera membawa anak ke rumah sakit jika terdapat keluhan yang serius agar dapat segera ditangani.